Correlation of Percentage of Body’s Fat of Breasfeeding Mother to Aterm Infant With Fat Content and Breast Milk Protein - Rosmaria Rosmaria (Universitas Andalas, 2018)
Maternal nutritional status is very important to be prepared properly because it correlates with breast milk production, quality and quantity of breast milk component and it has an important role to succesfully achieve breastfeeding that its indicators can be measured based on the duration of exclusive breast milk, infant development. Various studies show that there were positive relations of maternal nutritional status to breastfeeding performance and infant development.The method of this study applied cross sectional, with correlative study type to 48 postpartum mothers who breastfeed with exclusive breast milk to their infants aged 1-3 months. The study was conducted at work area of Belimbing Public Health Center and Central General Hospital of M Djamil from October to June 2016. The samples weere selected based on probality Sampling. The measurement of the percentage of body’s fat of breastfeeding aterm infant applying Bioelectrical Impedance Analysis (BIA). The measurement of fat content and breast milk protein with Human Milk Analizer Data Analysis of regression linear and Spearman.The results of the study show that there was a weak negative correlation and significant between the percentage of body’s fat of breastfeeding mother to aterm infant of breast milk fat content (r = - 0.33 ; p = 0.02). There was a very weak negative correlation and insignificant of breast milk protein content (r = - 0.33 ; p = 0.02).In conclusion, the higher the percentage of body’s fat of breastfeeding mother the lower of fat content and breast milk protein